We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

t(x')(t)+x(t)=t^2

I have the following problem and i know the answer is x(t)=(t^2/3)+(C/t)

I don't know the steps.

An explanation would be greatly appreciated

Spac3 Apr 28, 2018

#1**+1 **

Solve t ( d^2 x(t))/( dt^2) + 2 ( dx(t))/( dt) = 2 t:

Let ( dx(t))/( dt) = v(t), which gives ( d^2 x(t))/( dt^2) = ( dv(t))/( dt):

Divide both sides by t:

( dv(t))/( dt) + (2 v(t))/t = 2

Let μ(t) = e^( integral2/t dt) = t^2.

Multiply both sides by μ(t):

t^2 ( dv(t))/( dt) + (2 t) v(t) = 2 t^2

Substitute 2 t = d/( dt)(t^2):

t^2 ( dv(t))/( dt) + d/( dt)(t^2) v(t) = 2 t^2

Apply the reverse product rule f ( dg)/( dt) + g ( df)/( dt) = d/( dt)(f g) to the left-hand side:

d/( dt)(t^2 v(t)) = 2 t^2

Integrate both sides with respect to t:

integral d/( dt)(t^2 v(t)) dt = integral2 t^2 dt

Evaluate the integrals:

t^2 v(t) = (2 t^3)/3 + c_1, where c_1 is an arbitrary constant.

Divide both sides by μ(t) = t^2:

v(t) = (2 t)/3 + c_1/t^2

Substitute back for ( dx(t))/( dt) = v(t):

( dx(t))/( dt) = (2 t)/3 + c_1/t^2

Integrate both sides with respect to t:

x(t) = integral((2 t)/3 + c_1/t^2) dt = t^2/3 - c_1/t + c_2, where c_2 is an arbitrary constant.

Simplify the arbitrary constants:

**x(t) = t^2/3 + C1/t + C2. [Courtesy of Mathematica 11 Home Edition]**

Guest Apr 28, 2018